2021
DOI: 10.1371/journal.ppat.1009508
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota–host communications: Bacterial extracellular vesicles as a common language

Abstract: Both gram-negative and gram-positive bacteria release extracellular vesicles (EVs) that contain components from their mother cells. Bacterial EVs are similar in size to mammalian-derived EVs and are thought to mediate bacteria–host communications by transporting diverse bioactive molecules including proteins, nucleic acids, lipids, and metabolites. Bacterial EVs have been implicated in bacteria–bacteria and bacteria–host interactions, promoting health or causing various pathologies. Although the science of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 130 publications
(240 reference statements)
1
133
0
Order By: Relevance
“…However, the isolation and characterization of the heterogeneous profile of the gut microbiota are far more complex. As it was pointed out by other authors [ 95 ], a major obstacle is the lack of bacterial EV universal markers and their size-similarities to mammalian EVs, which complicate their separation from mammalian EVs in corporal fluids. Nevertheless, research continues to overcome these limitations, and recently Lagos et al [ 75 ] isolated and characterized EVs from pig gut microbiota in vitro, and new methods have been developed to isolate more effectively bacterial EVs from body fluids [ 124 ].…”
Section: Role Of Gut Microbiota and Probiotic-derived Extracellular Vesicles On Inflammation Obesity And Diabetesmentioning
confidence: 99%
“…However, the isolation and characterization of the heterogeneous profile of the gut microbiota are far more complex. As it was pointed out by other authors [ 95 ], a major obstacle is the lack of bacterial EV universal markers and their size-similarities to mammalian EVs, which complicate their separation from mammalian EVs in corporal fluids. Nevertheless, research continues to overcome these limitations, and recently Lagos et al [ 75 ] isolated and characterized EVs from pig gut microbiota in vitro, and new methods have been developed to isolate more effectively bacterial EVs from body fluids [ 124 ].…”
Section: Role Of Gut Microbiota and Probiotic-derived Extracellular Vesicles On Inflammation Obesity And Diabetesmentioning
confidence: 99%
“…OMVs and BEVs secreted by microbes serve a variety of intra-kingdom functions, including horizontal gene transfer, quorum sensing, biofilm formation, pathogenicity, depredation, antibiotic resistance, defense, and nutrient acquisition [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 38 , 60 , 61 ]. Similar to miRNAs, every bacterial sRNA and tRNA fragment is predicted to have multiple targets, can regulate genes in cis and trans, modulates transcription and translation, and affects mRNA stability [ 2 ].…”
Section: Extracellular Vesicles Secreted By Bacteria Are Important Mediators Of Inter-kingdom Communication and Deliver Srna And Trna Framentioning
confidence: 99%
“…Numerous studies have demonstrated that extracellular vesicles (EVs) play an important role in cell-cell signaling in all three domains of life, and that EVs are an important mechanism of intra-kingdom and inter-kingdom communication, including communication between hosts and pathogens (reviewed in [1][2][3][4][5][6][7][8][9][10][11][12][13]). The secretion of EVs as a mechanism of intra-kingdom and inter-kingdom communication is evolutionarily conserved, as cells from prokaryotes, plants, and animals release EVs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations